'Reluctant pioneer': A qualitative study of doctors' experiences as patients with long COVID - Anna K. Taylor; Tom Kingstone; Tracy A. Briggs; Catherine A. O'Donnell; Helen Atherton; David N. Blane; Carolyn A. Chew‐Graham (Wiley, 2021)
Abstract Background The coronavirus disease (COVID‐19) pandemic has had far‐reaching effects upon lives, healthcare systems and society. Some who had an apparently 'mild' COVID‐19 infection continue to suffer from persistent symptoms, including chest pain, breathlessness, fatigue, cognitive impairment, paraesthesia, muscle and joint pains. This has been labelled 'long COVID'. This paper reports the experiences of doctors with long COVID. Methods A qualitative study; interviews with doctors experiencing persistent symptoms were conducted by telephone or video call. Interviews were transcribed and analysis conducted using an inductive and thematic approach. Results Thirteen doctors participated. The following themes are reported: making sense of symptoms, feeling let down, using medical knowledge and connections, wanting to help and be helped, combining patient and professional identity. Experiencing long COVID can be transformative: many expressed hope that good would come of their experiences. Distress related to feelings of being 'let down' and the hard work of trying to access care. Participants highlighted that they felt better able to care for, and empathize with, patients with chronic conditions, particularly where symptoms are unexplained. Conclusions The study adds to the literature on the experiences of doctors as patients, in particular where evidence is emerging and the patient has to take the lead in finding solutions to their problems and accessing their own care. Patient and Public contribution The study was developed with experts by experience (including co‐authors HA and TAB) who contributed to the protocol and ethics application, and commented on analysis and implications. All participants were given the opportunity to comment on findings.